Analysis of Al-Si Layer on Steel Sheet during Thermo Mechanical Processing Using Microscopic Methods - Kusmierczak, Sylvia; Slavik, Michal (Manufacturing Technology Journal, 2018)
High strength steel 22MnB5 according to DIN EN 10083-3 belongs to the group of HF steels frequently used in the production of coachwork. Using the thermo mechanical pressing can be achieved that these steels have strength of about 1500 MPa. The surface of this steel is provided with a protective coating to protect it from oxidation. Galvanic ally, a Zn-based layer is used to provide cathodic protection. The Zn-based layer is limited by the temperature which is insufficient for TMP. Hot-dip galvanizing is also applied to an Al-based layer that does not serve as a cathodic protection but is used as an effective oxidation barrier. The quality of the Al-Si layer is important with regard to the resulting quality of the formed blank. The properties of the surface Al-Si layer affect not only the conditions for their application to the steel blank but also the external conditions which are determined by the conditions of the thermo-mechanical processing into the shape of the finished product. To assess the properties of this layer, microscopy methods, namely light and electron microscopy, were used. On the basis of analyzes, conclusions were drawn that should lead to securing the Al-Si layer with the required properties.
Keywords: Light Microscopy; electron Microscopy; Al-Si Layer; Properties